Covid-19 Community Mitigation Status at Selected Districts of Southwest Ethiopia: A Mixed Design Survey - Lakew S; Gilano G; Feleke T (Dove Medical Press, 2021)
Serawit Lakew,1 Girma Gilano,2 Tesfaye Feleke3 1Maternal-Reproductive Health Nursing, College of Medicine and Health Sciences, Nech Sar Campus, Arba Minch University, Arba Minch, Southwest Ethiopia, Ethiopia; 2Health Informatics, School of Public Health, College of Medicine and Health Sciences, Nech Sar Campus, Arba Minch University, Arba Minch, Southwest Ethiopia, Ethiopia; 3Health Education in School of Public Health, College of Medicine and Health Sciences, Nech Sar Campus, Arba Minch University, Arba Minch, Southwest Ethiopia, EthiopiaCorrespondence: Serawit LakewMaternal-Reproductive Health Nursing, College of Medicine and Health Sciences, Nech Sar Campus, Arba Minch University, Arba Minch, Southwest Ethiopia, EthiopiaTel +251 913273829Email lserawit@yahoo.comBackground: The spread of covid-19 was alarmingly continued in Ethiopia. This survey assessed the status of community mitigations to fight the pandemic. The ongoing forward effort by local task forces can be assessed to note the achievements.Methods: A mixed design using quantitative and qualitative triangulations used. Data was collected through interviewer administration using a structured W.H.O tool. The univariate and bivariate analysis employed to analyze descriptive statistics. The logistic regression model was applied to control confounders and determine potent predictors.Objective: This study assessed community mitigation status on covid-19 pandemic at four selected districts of southwest Ethiopia: a mixed design survey.Results: From the total of 624 participants interviewed, nearly half reported good mitigations toward fighting the covid-19 epidemic. This study suggested that nearly half (54.2%) of the participants had good knowledge about the newly emerged epidemic symptoms. Three out of five participants had good Knowledge of preventive practices (63.1%). Nearly four out of five (72.6%) participants were knowledgeable about 14 days incubation period. The odds of having good mitigation to prevent covid-19 among the participants who had single marital status were 55% lower than those married union (AOR=0.45, 95% CI: 0.24, 0.86). The odds of having good mitigation to prevent covid-19 among the participants (good knowledge symptoms) were 3.4 times higher than those with poor knowledge (AOR= 3.39, 95% CI: 2.19, 5.23).Conclusions and Recommendations: Participants’ mitigation status to fight covid-19 was promising. Handwashing with soap and water, disinfecting surfaces, and covering mouth or nose while coughing were mitigated practices by the vast majority. Home staying was the least mitigated practice. Participants’ demographic status, knowledge of the epidemic symptoms, and knowledge of preventive measures were potent predictors of mitigations to fight covid-19. HID services should be extended to the rural population through HCWs and task forces.Keywords: covid-19, mitigation, community, Gamo, Southwest Ethiopia